Pemikiran Modern Tentang Pendidikan - Tasya Aryati Sakinah; Rafiqah Alya; Ahmad Azim (Jurnal Bintang Pendidikan Indonesia, 2025)
Education is a fundamental element in human resource development which plays a significant role in the nation's progress. As time goes by, various modern ideas about education have emerged which aim to improve the quality of learning and its relevance to society's needs. This article discusses several modern educational approaches, including environmental-based teaching, project-based learning, homeschooling, work schools, character education, and inclusive education. Each approach is analyzed based on its benefits, challenges and contribution to the formation of a holistic individual. In conclusion, the integration of these various methods in the education system can create a generation that is adaptive, creative and has high social responsibility.